Tuha Peut's Empowerment Strategy Through the Implementation of Qanun Concerning the Prevention of Cakes to Pregnant Women in Macah Village, Suka Makmue District, Nagan Raya Regency - Fari ajani; Fitriani (Jurnal EduHealth, 2022)
Pregnancy is the dream of humans for the future. In the next period, nutrition is a serious factor for pregnant women that will be faced by the Indonesian people, namely the problem of SEZ in pregnant women, women who are affected by diabetes will affect their pregnancy in prospective babies. Empowerment of Tuha peut in implementing Qanun in maintaining KEK for all pregnant women in Nagan Raya. This study applies a work method that is centered on interviews, observation and document utilization which is called descriptive qualitative. Handling of cakes in the village of Nagan Raya has been running as it should which can help pregnant women to avoid SEZ problems with a program that runs regularly and continuously. Treatment strategies are needed so that treatment can be maximized.